A time domain discrete-module-beam-bending-based hydroelasticity method for the transient response of very large floating structures under unsteady external loads. (15th September 2018) - Zhang, Xiantao; Lu, Da; Gao, Yun; Chen, Lifen
Abstract: A time domain method is developed for estimating the transient response of very large floating structures under unsteady external loads. The hybrid frequency-time domain approach based on Cummins equations is adopted. First, the discrete-module-beam-bending-based hydroelasticity method in which a flexible structure is discretised into several rigid submodules connected by beam elements is used to establish the equations of motion for a flexible structure in frequency domain. The equations of motion in frequency domain are transformed into time domain following the idea of Cummins equations. The unsteady external loads at any point of the flexible structure are transferred to the centre of gravity of each submodule using the hydrostatic analysis of a beam in calm water. Good agreements are obtained between the numerical and experimental data for a weight drop test and a moving point load test of a continuous flexible structure in calm water, which validates the present time domain method. Finally, the time domain method is used for simulating the transient response of an interconnected flexible structure under the combination of wave and unsteady external loads, which highlights the significant effects of moving point loads on both the vertical displacement and bending moment of the structure. Highlights: A time domain discrete-module-beam-bending hydroelasticity method is developed for transient response of a VLFS. An approach is proposed for determining the natural frequency of an interconnected flexible structure. An effective strategy is proposed for dealing with the unsteady external loads for the time domain method. Effects of moving loads on hydroelastic response of a hinged VLFS in waves are highlighted by numerical results.